Translating vitamin D transcriptomics to clinical evidence: Analysis of data in asthma and chronic obstructive pulmonary disease, followed by clinical data meta-analysis. Issue 197 (March 2020) - Malliaraki, Niki; Lakiotaki, Kleanthi; Vamvoukaki, Rodanthi; Notas, George; Tsamardinos, Ioannis; Kampa, Marilena; Castanas, Elias
Highlights: Vitamin D research in different human pathologies has produced highly variable and divergent results. Using a novel methodology (c-SKL), we analyzed all reported data and compared vitamin D-induced changes with human pathologies, in an unbiased manner. After validation of the method with osteoporosis data, we concentrated on two of the conditions with the highest correlation, Chronic Obstructive Pulmonary Disease (COPD) and asthma. Common gene analysis did not identify any known pathway, significantly linking the two conditions (Vitamin D administration and asthma or COPD). FEV1 % meta-analysis of published observational or intervention studies confirmed the absence of a beneficial role for Vitamin D in both asthma and COPD. Abstract: Vitamin D (VitD) continues to trigger intense scientific controversy, regarding both its bi ological targets and its supplementation doses and regimens. In an effort to resolve this dispute, we mapped VitD transcriptome-wide events in humans, in order to unveil shared patterns or mechanisms with diverse pathologies/tissue profiles and reveal causal effects between VitD actions and specific human diseases, using a recently developed bioinformatics methodology. Using the similarities in analyzed transcriptome data (c-SKL method), we validated our methodology with osteoporosis as an example and further analyzed two other strong hits, specifically chronic obstructive pulmonary disease (COPD) and asthma. The latter revealed no impact of VitD on known molecular pathways. In accordance to this finding, review and meta-analysis of published data, based on an objective measure (Forced Expiratory Volume at one second, FEV1 %) did not further reveal any significant effect of VitD on the objective amelioration of either condition. This study may, therefore, be regarded as the first one to explore, in an objective, unbiased and unsupervised manner, the impact of VitD levels and/or interventions in a number of human pathologies.